Political conflict on spatial practice at urban parks in Turkey: Cases af Ankara and İstanbul - İlkay, Yasemin (AESOP, 2017)
Urban parks are defined as ‘green’, ‘open’ and ‘public’ spaces where citizens recreate themselves; interact with nature and each other. Furthermore, (as lived spaces) parks provide a backcloth for spatial practices and (re)produce urban everyday life via framing daily rhythms and behaviours within their physical boundaries. Nonetheless, urban parks (as conceived spaces) are regulated via official decisions of the state, especially by the hand of local governments, which implies the spatial policy of the party in power and capital accumulation process rather than use value of inhabitants and spatial quality of natural-built environment. Indeed, spatial policy is fragile particularly in the countries like Turkey, since it is extremely influenced by the political-economic shifts. Moreover, neo-liberal spatial policies stretched the limits and definitions of public and private spaces; which led to both deformation of open-green areas and privatization of public spaces. We can follow a disruption and displacement process within urban public spaces and green areas especially in the cases of Ankara and İstanbul, two great cities of Turkey. As an essential example, Ankara was conceived and re-designed delicately in 1920s as the capital of newly-established nation-state which has both a spatial and political essence in the planning history of Turkey. The re-creation of Ankara served for not only creating new publics with their (public) spaces but also constituting the examples of modern city planning in new Turkish Republic (i.e. Gençlik Park [meaning Youth Park, one of many examples constructed in several other Turkish cities in early-republican period] and Güvenpark [the name of the park means ‘safety’, ‘trust’; it was designed with a symbolic-political content and formed as a part of both the master plan of the city (Jansen Plan) and micro design of the city–centre]). However, public space pattern of the city has been gradually disrupted in the following decades. Rather than staying in and practicing publicness, citizens tend to pass through open public spaces, which is partly a result of incremental and arbitrary approaches to the design and construction. Moreover, the political-symbolic displacement process –during the reproduction of open public spaces and urban greenery– led to a decrease in the socio-spatial quality of such spaces. On the contrary to the first era of early-republican period, dysfunctional and poor-quality public spaces have been constructed and reproduced through plans, codes and projects of decision makers hand in hand with market mechanisms though their recreational and public potentials via urban daily experience.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017